Desain Taman Sekolah untuk Anak Berkebutuhan Khusus di Sekolah Alam Bogor - Jasmine Kashmira Izdihar; Dewi Rezalini Anwar (http://arl.faperta.ipb.ac.id/, 2019)
The condition of a school landscape is important because it affects the learning process which can increase participation among students. Nature school is one form of an educational institution that takes account the importance of a landscape and how the students can appreciate the environment. One nature school is in Bogor, more specifically at Tanah Baru. This nature school has an inclusive education program for children with special needs, in which they can interact with other children of the same age. The aim of this research is to create a concept and design of the school landscape and playgrounds that can function as an educational and healing space through programs and activities that stimulate growth and development of children with environmental qualities and esthetics. The method that was used for this research was analyzing qualitative and quantitative aspects through three approaches that are biophysics, social, and education of special needs children. This method was done through four stages which are: (1) preparation stage, (2) research and analyzing the existing conditions (physical and biophysical) and educational process for special needs children through direct observation and literature review, (3) data processing stage, and (4) designing stage. The main concept of this school landscape is to create an educational and interactive landscape which can be used for therapeutic activities by combining the existing therapeutic activities. The main concept of this landscape comes from the concept “building blocks for learning” which consists of skills obtained from therapeutic activities. The design concept, “building blocks of life”, is a development from the main concept which can be interpreted as the compositional structure of all living things, in which cells are the lowest structural level of living things, as well as elementary school in the educational system. The output of this research is limited to the landscape design phase, with the final product in the form of a site plan and other supporting detail drawings.